European Cancer Summit 2022 submission for Special Network: Impact of the Covid-19 Pandemic on CancerImpact of the COVID-19 Pandemic on Cancer Surgery and Cancer Mortality in England. (March 2023) - Connor, Katie; Hinchliffe, Rosie; Barclay, Lorna
Abstract: Background: During the pandemic there has been an impact on the number of patients entering the cancer pathway, because of changes in patients presenting and GP referral behaviours. The aim was to understand whether different groups in our society have been disproportionately affected by the pandemic in terms of the care they have received for their cancer. Methods: The study looked specifically at elective admissions from the Hospital Episode Statistics data for all cancers combined and separately for breast, bowel, lung, and prostate cancers to investigate the number of patients admitted for cancer surgery over time. The ONS Mortality Dataset was used to investigate the place of death for patients who had died from cancer. Mortality rates were calculated to identify whether there was a rise in in-hospital mortality during the pandemic. Deaths were defined as an in-hospital death for a patient admitted with a primary diagnosis of cancer. Age-standardised mortality rates were created across the last five years, broken down by cancer type, sex and deprivation quintile. Results: The analysis shows a decrease in patients undergoing surgery at the start of the pandemic for all demographic groups. At the start of the pandemic, the largest decreases for all cancers combined by ethnicity could be seen in White (42.6%) and Asian or Asian British (44.6%). While by age, the largest decrease was seen in women aged 40-49. For lung cancer surgery, there were differences by deprivation quintile during the recovery period, showing a 42.0% increase in the least deprived compared to a 27.6% increase in the most deprived. However, changes at the beginning of the pandemic were similar across all quintiles. Age standardised mortality rates showed an increase in in-hospital deaths following the start of the pandemic. Conclusions: While we know that there are inequalities in access to cancer surgery, particularly by age, for the most part, the results of our analysis indicate that the recovery period of the COVID-19 pandemic has not exacerbated these inequalities. However, it is difficult to understand the extent to which any variation in access to cancer services is unwarranted.